2018
DOI: 10.1038/s41565-018-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive, stretchable and biocompatible Ag–Au core–sheath nanowire composite for wearable and implantable bioelectronics

Abstract: Wearable and implantable devices require conductive, stretchable and biocompatible materials. However, obtaining composites that simultaneously fulfil these requirements is challenging due to a trade-off between conductivity and stretchability. Here, we report on Ag-Au nanocomposites composed of ultralong gold-coated silver nanowires in an elastomeric block-copolymer matrix. Owing to the high aspect ratio and percolation network of the Ag-Au nanowires, the nanocomposites exhibit an optimized conductivity of 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
486
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(512 citation statements)
references
References 38 publications
1
486
0
1
Order By: Relevance
“…In addition to the supporting materials, the development of biocompatible active materials is also essential. For example, Choi et al reported a highly conductive and biocompatible Ag‐Au NW composite for implantable electrophysiological sensors (Figure A) …”
Section: Novel Properties Of Skin‐inspired Physical Sensorsmentioning
confidence: 99%
“…In addition to the supporting materials, the development of biocompatible active materials is also essential. For example, Choi et al reported a highly conductive and biocompatible Ag‐Au NW composite for implantable electrophysiological sensors (Figure A) …”
Section: Novel Properties Of Skin‐inspired Physical Sensorsmentioning
confidence: 99%
“…G, Conductivity evolution of the two types of composites at the same weight ratio of nanowire:SBS of 80:20. Reproduced with permission . Copyright 2018, Nature Publishing Group.…”
Section: Nanowire Electronicsmentioning
confidence: 99%
“…From another viewpoint, hybrid nanowires can be treated as a simple integration of the advantages of the different components. For example, Au and CuNi have been wrapped around AgNWs and CuNWs, respectively, to realize high conductivity nanowire interconnects with better stability . As a structural protection layer and electrical shielding, SiO 2 and Al 2 O 3 have been frequently applied as nanowire shells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Also, fully rubber conductive materials that show quite good van der waals adhesion to the human skin have been used for wearable sensing/actuating applications. [18] However, in comparison with the prosperity of research on strain sensors, there have been rare reports on the curvature sensors that can measure bending deformation, although accurate dynamic measurement of curvature is of great interest: it is especially useful for detection of activities of some special body parts such as spines and finger/elbow/knee/ankle joints.…”
Section: Introductionmentioning
confidence: 99%